2016
DOI: 10.1136/vr.103433
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and impact of dog attacks on guide dogs in the UK: an update

Abstract: 9Data on dog attacks on Guide Dogs' stock were reviewed to investigate the 10 characteristics of the attacks. An average of 11.2 attacks occurred each month. 11Nearly all of the attacks occurred in public areas, 68.4% of victim dogs were 12 qualified guide dogs and 55.5% of victim dogs were working in harness when they 13 were attacked. Guide Dogs' stock were injured in 43.2% of attacks and veterinary 14 costs for attacks were estimated at £34,514.30. Over 40% of qualified guide dogs' 15 working ability was af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
6
0
4
Order By: Relevance
“…It is concerning that almost a quarter of respondents found that their dogs subsequently became distracted by other dogs as a result of the encounter. The number of dogs that had to be retired as a result of an aggressive encounter was similar in proportion to that reported in the most recent Guide Dogs UK retrospective survey, in which 3% of dog guides (13 of 430) had to be retired after being attacked by another dog (Moxon et al, 2016). Although this number is relatively low, it is too high when one considers the resources that are necessary to create and maintain dog guide partnerships, not to mention the effect on the welfare of the dog and the social and emotional well-being of the dog guide handler.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It is concerning that almost a quarter of respondents found that their dogs subsequently became distracted by other dogs as a result of the encounter. The number of dogs that had to be retired as a result of an aggressive encounter was similar in proportion to that reported in the most recent Guide Dogs UK retrospective survey, in which 3% of dog guides (13 of 430) had to be retired after being attacked by another dog (Moxon et al, 2016). Although this number is relatively low, it is too high when one considers the resources that are necessary to create and maintain dog guide partnerships, not to mention the effect on the welfare of the dog and the social and emotional well-being of the dog guide handler.…”
Section: Discussionsupporting
confidence: 73%
“…There is a small body of literature concerning the frequency and effect of dog attacks on dog guide handlers (Brooks et al, 2010; Godley & Gillard, 2011; Kutsch, 2011; Moxon et al, 2016). This literature has raised awareness about the significant implications of attacks by dogs on dog guides and their handlers.…”
mentioning
confidence: 99%
“…Additionally, 12 dogs with green flags were later withdrawn from the program. Due to the large impact of environment on dog-behavioural development [36] we would hypothesis that after their assessments these dogs may have had a life-experience that altered their behaviour (for example a dog-attack, see [37,38]) or that they had singularly good scores for one trait and poor scores for others that led them to have an overall profile unsuitable to guiding work. Due to the heterogeneous nature of withdrawal reasons, this analysis considered each trait scale separately, but it is hoped that when in use by Guide Dogs that a dog’s behaviour profile across all traits could be considered on a case-by-case basis.…”
Section: Discussionmentioning
confidence: 99%
“…Dog bites account for hundreds of thousands of emergency hospital visits annually, and children are particularly at risk ( 1 – 3 ). Dog–dog aggression is a widespread community concern ( 4 ), and it further increases the number of dog–human bites since many human bites occur when people try to separate fighting dogs ( 5 ). Aggression is a common reason for euthanasia of adult dogs ( 6 ).…”
Section: Introductionmentioning
confidence: 99%